(3bUjOI aj GdZRds - (3GdTjN eMehOs ((3HNW GdeDdas)
(3ChdgG (B:s
(3eG CQTafj GdMH QGM YVbc aj CdMGf GdChhJQZJ aj ghGc HCdMGfs
(3BNQgG (B:s
(3hGNJe HGdUdGI Ydjg Ke SdGe (B*** (3eG ZQOJ GdhQb aj NeGFd CZUGfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdCOHs